High respiratory virus oropharyngeal carriage rate during Kingella kingae osteoarticular infections in children. (January 2015) - Basmaci, Romain; Bonacorsi, Stéphane; Ilharreborde, Brice; Doit, Catherine; Lorrot, Mathie; Kahil, Mahmoud; Visseaux, Benoît; Houhou, Nadhira; Bidet, Philippe
ABSTRACT : Aim: Kingella kingae osteoarticular (KKO) infections are frequently associated with upper respiratory tract infections. However, no comparative studies detecting respiratory viruses had ever been performed between KKO and non-KKO (NKO).Patients & methods: Eighteen viruses were searched by FilmArray ® Respiratory Panel (BioFire Diagnostics, UT, USA) in the oropharynx of 6-to-48-month-children admitted for KKO and NKO in 2013.Results: At least one virus was detected in the oropharynx of 19/21 (90.5%) KKO and 3/8 (37.5%) NKO cases (p = 0.008). In KKO group, human rhinovirus was predominant (12/21; 57.1%), especially during winter (7/11; 63.6%) despite its low concomitant circulation (<10%). Human rhinovirus was found in 2/8 (25%) in NKO group.Conclusion: Higher prevalence of respiratory virus in oropharynx was observed in KKO than NKO, strengthening their putative role in KKO pathophysiology.